ANALISIS EFEKTIVITAS PENGELOLAAN DANA BANTUAN RINTISAN SEKOLAH STANDAR NASIONAL (RSSN) DI SMA NEGERI 1 MARISA KABUPATEN POHUWATO - Muhammad Anas (AkMen JURNAL ILMIAH, 2014)
The research problem is " Does Aid Management School Pilot National Standard ( RSSN ) at SMA Negeri 1 Marisa Pohuwato been effective ".The results of the processing of data about respondents at SMAN 1 of 8 items Marisa question / statement obtained 7 items or 87.50 % who answered that the grant management school stubs National Standard is effective.